In-situ synthesis of graphene-like carbon encapsulated copper particles for reinforcing copper matrix composites. (May 2021) - Shu, Shengcheng; Yuan, Qilong; Dai, Wen; Wu, Mingliang; Dai, Dan; Yang, Ke; Wang, Bo; Lin, Cheng-Te; Wuebben, Thomas; Degenhardt, Jost; Regula, Christoph; Wilken, Ralph; et al.
Abstract: Owing to the unfavorable wetting and density difference between graphene and copper, it remains challenging to achieve homogeneous dispersion of graphene for utilizing the unique nature of graphene in copper matrix composites. Here, we design an in-situ process to fabricate graphene-like carbon (GLC) reinforcing copper matrix composites: GLC can be directly fabricated on commercial copper particles using modified PECVD method followed by vacuum hot pressing, which is high-efficiency and can be massively produced for graphene reinforced metal matrix composites in industrial level. After hot pressing, the GLC with ultralow content (170 to 350 ppm) can be uniformly dispersed and tightly embedded within the copper matrix. A remarkable thermal conductivity enhancement efficiency of 85% and enhanced thermal conductivity (439 W m −1 K −1 ), accompanied by the higher wear resistance, can be obtained in our GLC reinforced copper matrix composites. In actual arc ablation performance measurement, the breakdown strength and relative arc ablation resistance of GLC/Cu composites can be significantly improved by 106.5% and 33.3% than pure copper, respectively, demonstrating GLC/Cu composites a promising candidate for application as high voltage electrical contacts. Graphical abstract: Unlabelled Image Highlights: A facile method for in-situ synthesis of graphene-like carbon reinforced copper matrix composites is developed. A remarkable thermal conductivity enhancement efficiency and enhanced thermal conductivity can be achieved. The graphene-like carbon reinforced composites demonstrate a promising candidate for application as electrical contacts. This work provides an efficient synthesis method for mass production of graphene reinforced metal matrix composites.